Hubungan Hasil Belajar Teori Musik Dasar Dengan Keterampilan Bermain Musik Dalam Ansambel - Rhiyan Anosya Bahtera; Syeilendra Syeilendra (LPPM Politeknik Pratama, 2023)
The goal of this study was to determine how the FBS UNP Sendratasik Study Program students' 2020 ensemble music playing abilities and the learning objectives of their foundational music theory courses related to one another. This kind of study employs the correlation test method and is quantitative in nature. Student observation sheets, surveys, and questionnaires were the research instruments used in this study. Data were gathered by observation, interviews, questionnaires, literature and document studies, and surveys. The formula for product moment correlation was used to analyze the data. The results of the study prove that the relationship between the learning outcomes of basic music theory courses and the skills of playing music in ensembles of 2020 class music concentration Sendratasik Education Study Program students who have completed basic music theory courses and ensemble courses get a correlation coefficient (r) value of 0.210251933 or percented to 21.02% which is categorized as weak.